The key moment in the genesis of mobile cellular systems. Control of radio links in universal mobile cellular systems - Pasarelska, Teodora; Pasarelski, Rosen (Yearbook Telecommunications, 2022)
The most crucial moment in the genesis of mobile cellular systems is the implementation of a universal telecommunications system, as one of its most important aspects is to integrate existing second-generation cellular standards into a single platform. Universal mobile systems are based on several different standards, one of which is WCDMA. It is compatible with the widespread GSM technology and uses a bandwidth between 5 MHz and 10 MHz, thus creating a stable platform for deploying applications using wide bandwidth. The purpose of this article is to present the main emphasis in the control of radio communications in universal mobile cellular systems. To systematize the protocols used in the layers related to radio control and to summarize their basic functions. Control processes such as radio interface measurements, handover, borrowing, reconfiguring, and releasing radio resources needed by one radio link and others are affected.